Pengembangan Media Miniatur Pada Pembelajaran Pendidikan Agama Islam materi Ibadah haji kelas IX SMP Negeri 2 Tanalili - Anggi, Anggi Wulandari (South Sulawesi Education Development, 2024)
This thesis discusses the Development of Miniature Media in Islamic Religious Education Learning Hajj Material in class IX of Smpn 2 Tanalili.The main problems in this research are:1) How to develop miniature-based learning media for the eye PAI lessons on Hajj material in class IX SMPN 2 Tanalili. 2) What are the stages of developing miniature-based learning media in PAI subjects, Hajj material in class IX of SMPN 2 Tanalili. 3) What is the practicality of miniature media in PAI subject matter? Hajj in class IX of SMPN 2 Tanalili. This research aims to provide an overview of development procedures Miniatures on Islamic Religious Education Learning Hajj Material in class IX Smpn 2 Tanalili is valid and practical.This type of research is development research (R&D) for produces miniature products for Islamic Religious Education Learning Hajj material in class IX Smpn 2 Tanalili. Researchers use the Borg and model Gall which has been described by Sugiyono with the abbreviation seven stages development, namely: (1) Potential and problems, (2) Data collection, (3) Design product, (4) Validation, (5) Design revision, (6) Product testing, (7) Product Revision. The results of this research show that: 1) Media development The learning used is research, development, R&D with using research steps by Sugiyono which were modified from the research development of Borg and Gall through 7 stages, namely potential and problems, data collection, product design, design validation, design revision, product testing and product revisions. 2) Results of the validity of miniature learning media developed on Hajj pilgrimage material obtained media validation results of 91.6% with a very valid category, and results from material expert validation were obtained validation results were 97.5% with a very valid category. Therefore This miniature media has an average score of 94.5% with a very valid category. 3) Based on the results of practicality tests for educators and students, learning media Miniatures developed by each researcher get a percentage 97.5% of educators and an average percentage of 87.25% of students, so Miniature media meets the practicality criteria in the very practical category. Keywords: Instructional Media, Miniature, Hajj